ASPEN definitions in pediatric intestinal failure. Issue 1 (15th September 2021) - Modi, Biren P.; Galloway, David P.; Gura, Kathleen; Nucci, Anita; Plogsted, Steven; Tucker, Alyssa; Wales, Paul W.
Abstract: Pediatric intestinal failure (PIF) is a relatively rare disease entity that requires focused interdisciplinary care and specialized nutrition management. There has long been a lack of consensus in the definition of key terms related to PIF because of its rarity and a plethora of small studies rather than large trials. As such, the American Society for Parenteral and Enteral Nutrition (ASPEN) PIF Section, composed of clinicians from a variety of disciplines caring for children with intestinal failure, is uniquely poised to provide insight into this definition void. This document is the product of an effort by the Section to create evidence‐based consensus definitions, with the goal of allowing for appropriate comparisons between clinical studies and measurement of long‐term patient outcomes. This paper has been approved by the ASPEN Board of Directors.